Pengembangan Instrumen Penilaian Afektif untuk Mengukur Sikap Siswa Terhadap Nilai atau Norma yang Berhubungan dengan Materi Keanekaragaman Hayati Indonesia - Marliza ,; Yusrizal ,; Abdullah , (Universitas Islam Negeri Ar-Raniry, 2015)
The aim of this research is to develop an instrument for affective assessment to measure students’ attitude on norms and values in the concept of Indonesian’s biological diversity. A developmental research was conducted from February to March 2015. The results showed that from 60 items of affective instruments of modified likert scale which was designed by the researcher and then validated by 3 experts’ lecturers, It was found that there were 44 triable instruments. From 44 items that have been tried out to 272 respondents, there were only 12 invalid items with the coefficient of correlation was ≤ 0.3. The reliability of the item was 0.868 which was categorized as good. After the next trial, 32 items of instrument were tried out to 100 respondents to measure students’ attitudes. It was found that the average of students’ attitude was 103.97 which was considered as having positive attitudes. It can be concluded that the quality of developed-likert scale item instrument for assessing affective domain has been valid and reliable. It has fulfilled the criteria of a good tool to assess attitude domain.